Pengaruh Pendidikan Kesehatan dengan Media Buku KIA terhadap Tingkat Pengetahuan Ibu Hamil tentang Tanda Bahaya Kehamilan - Yeni Susanti; Alfi Noviyana (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
According data to World Health Organization (WHO) in 2020 stated that in developed countries the number of maternal mortality rates reached 11/100,000 live births and maternal mortality rates in developing countries were 462/100,000 live births (WHO, 2022). According to the Indonesian Demographic and Health Survey (SDKI) Data, the number of maternal mortality rates in 2020 showed 4,627 deaths in Indonesia. The number of maternal mortality cases in Central Java Province based on data from the Central Java Health Office (2020) was 421 cases (Central Java Health Office, 2020). The number of maternal mortality rates in 2023 in the Cilacap Regency Health Office Area was 14 people (Cilacap Regency Health Office, 2023). The prevalence of maternal mortality rates in the Kawunganten Health Center Work Area in 2024 was 3 cases caused by 1 case of PEB, 1 case of bleeding, and 1 case of anemia Objective: To analyze the influence of health education using KIA book media on the level of knowledge of pregnant women about pregnancy danger signs in the Kawunganten Health Center Working Area.Method:This research uses a quantitative type with a designpre-experimental. This research design uses one group pretest-posttest. The population in this study was 84 pregnant women. The sampling technique in this study usedpurposive samplingand obtained 40 respondents who met the inclusion and exclusion criteria. The instrument in this study used a pregnancy danger signs questionnaire adopted from Iswidayanti's research (2219). Data analysis was carried out using the testWilcoxon with a significance level of 95%.Results: Health education using KIA book media has an influence on the level of knowledge of pregnant women about danger signs of pregnancy in the Kawunganten Health Center Work Area.p values 0.000<0.05. Conclusion :Health education using KIA book media has an effect on the level of knowledge of pregnant women about danger signs of pregnancy in the Kawunganten Health Center Working Area, Cilacap Regency.